Nuclear Magnetic Resonance (NMR) as A Method of Characterizing Antigen Synthesis for Successful Antibody Production - Assaat, Lusiani Dewi; Saepudin, Endang; Soejoedono, Retno Damayanti; Adji, Rahmat Setya; Fajriah, Sofa; Ivandini, Tribidasari Anggraningrum (EduChemia: Jurnal Kimia dan Pendidikan, 2023)
Antibody production is becoming a trend, especially during a pandemic like now, although there have been many developments in antibody production in previous research. Antigen synthesis and characterization is one of the determining factors for the success of antibody production. This research developed a method of antigen characterization using the Nuclear Magnetic Resonance (NMR) method. The research conducted in these 4 stages begins with antigen synthesis, then continues with antigen characterization using NMR, then antibody production, and the last stage is antibody characterization using the Enzyme Linked ImmunoAssay (ELISA) method. The results of antigen characterization using NMR show that NAS has been perfectly conjugated with BSA and produces a NAS-BSA conjugate. This is shown by the presence of 1 methylene (CH2) olefinic at δH chemical shift of 6.27 ppm with an integral of 4 and having 1 piece of methine (CH) sp2 at δH chemical shift of 5.73 ppm with an integral of 2. NAS-BSA antigens have been shown to successfully produce antibodies. This is shown from the anti-NAS-BSA, NAS, and Acrylamide antibodies that begin to appear in the second, third and fourth boosting (respectively)